Epidemiology and Outcomes of Early Morning Neuroparalytic Syndrome Following Snake Bite—A Retrospective Study. (18th February 2020) - Samprathi, Madhusudan; Gupta, Vipul; Jayashree, Muralidharan; Bansal, Arun; Baranwal, Arun; Nallasamy, Karthi
Abstract: Objective: Snake envenomation has been poorly studied in developing countries. 'Early morning neuroparalytic syndrome' (EMNS), the classical clinical constellation caused by krait bites, refers to nighttime, indoor bites where nonspecific symptoms progress to neuroparalysis. Literature regarding EMNS in children is scarce. This study was planned to describe the clinical profile, intensive care needs and predictors of outcome in children with EMNS. Methods: It is a retrospective study of children below 12 years admitted with a clinical diagnosis of snake envenomation to the pediatric intensive care unit (PICU) of a tertiary care hospital in North India. Patient records were reviewed from the electronic patient database manager. Comparison was made between the EMNS group and the non-EMNS group and between survivors and nonsurvivors within the EMNS group. Results: Of the 111 children with snake envenomation, 76 had neuroparalysis (68%) and 51 had EMNS. In the EMNS cohort, 37 (72.5%) belonged to rural areas, 46 (90.2%) had indoor bites and 39 (76.5%) were witnessed. Patients with EMNS were more likely to have absent fang marks, hypoxemia at admission, bulbar palsy and need for PICU admission. Mortality rate was 13.7% in EMNS; predictors included younger age, presence of ptosis, cardiac arrest at admission and nonavailability of PICU bed (univariable analysis) but none of them independently predicted mortality. Conclusion: Younger age, presence of ptosis, cardiac arrest at admission and nonavailability of intensive care beds increase the risk of mortality in children with EMNS. Timely recognition and respiratory support may reduce mortality in these children.